Equipment and methods for measuring reflectance of concentrating solar reflector materials - Fernández-García, Aránzazu; Sutter, Florian; Martínez-Arcos, Lucía; Sansom, Christopher L.; Wolfertstetter, Fabian; Delord, Christine (Elsevier, 2017)
The proper optical characterization of solar reflector materials is a challenging task. Although several commercial instruments exist to measure reflectance, they have been developed for other applications and often do not meet all the specific requirements demanded by the solar thermal industry. In particular, the characterization of solar reflectors involve the complete solar spectral wavelength range, an incidence angle range from near normal to 70° and most importantly a very narrow acceptance angle range from near specular to 20 mrad. The accurate measurement of reflectance as a function of all the previously mentioned parameters has not been commercially implemented. This paper reviews the different alternatives to measure reflector materials, describes reflectance models used to approximate the missing information and presents current research work on prototype reflectometers to fill the gap.
Keywords: Solar reflector; Concentrating solar technology; Reflectance measurement; Spectrophotometer; Reflectometer